PENINGKATAN KUALITAS KARYA ILMIAH MAHASISWA MELALUI PELATIHAN PENULISAN DENGAN MANAJEMEN REFERENSI “MENDELEY” - Heru Kurniawan; Maula Maratus Solikhah; Bambang Abdul Syukur (Universitas Mataram, 2026)
Students’ literacy culture remains largely instrumental, with reading activities primarily driven by academic assignments rather than intrinsic motivation, resulting in suboptimal use of scholarly resources for learning and personal development. This condition contributes to low-quality scientific writing and weak reference management skills. Therefore, a structured intervention through technology-based training is necessary to enhance academic literacy. This program aims to improve students’ ability to organize, cite, and share academic references effectively using reference management software. The method employed includes interactive lectures combined with question-and-answer sessions, dissemination of instructional posters, and provision of recorded learning materials via digital platforms. Evaluation was conducted through pre-test and post-test to assess participants’ competency improvement. The results indicate a significant increase in students’ understanding and skills in using reference management tools, as reflected by the improvement in scores from a mean pre-test of 62.72 to a post-test of 78.5. Furthermore, participants demonstrated greater confidence in producing structured and academically appropriate scientific writing. The program also fostered a shift in literacy perception from obligation to academic necessity. In conclusion, this training is effective in enhancing students’ academic literacy and reference management skills.